Optical Imaging of Dynamic Collagen Processes in Health and Disease - Iannucci, Leanne E.; Dranoff, Charles S.; David, Michael A.; Lake, Spencer P. (Frontiers in Mechanical Engineering, 2022)
Collagen is a major structural component of nearly every tissue in the human body, whose hierarchical organization imparts specific mechanical properties and defines overall tissue function. Collagenous soft tissues are dynamic structures that are in a constant state of remodeling but are also prone to damage and pathology. Optical techniques are uniquely suited for imaging collagen in these dynamic situations as they allow for non-invasive monitoring with relatively high spatiotemporal resolution. This review presents an overview of common collagen dynamic processes associated with human health and disease and optical imaging approaches that are uniquely suited for monitoring, sensing, and diagnosing these changes. This review aims to (1) provide researchers with an understanding of the underlying optical properties of collagen that can be leveraged for extracellular matrix visualization and (2) present emerging opportunities for machine learning driven analysis to drive multiscale and multimodality solutions.